Respuestas
Respuesta dada por:
0
Aplicas productos notables.
(a - b)² =
a² - 2ab + b²
(3 - c)² =
(3)² - 2(3)(c) + c² =
9 - 6c + c²
Aplicas.
(a + b)³ =
a³ + 3a²b + 3ab² + b³
(5 + z)³ =
5³ + 3(5)²z + 3(5)z² + z³ =
125 + 3(25)z + 15z² + z³ =
125 + 75z + 15z² + z³
(a - b)² =
a² - 2ab + b²
(3 - c)² =
(3)² - 2(3)(c) + c² =
9 - 6c + c²
Aplicas.
(a + b)³ =
a³ + 3a²b + 3ab² + b³
(5 + z)³ =
5³ + 3(5)²z + 3(5)z² + z³ =
125 + 3(25)z + 15z² + z³ =
125 + 75z + 15z² + z³
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años